Amidinium–carboxylate salt bridge mediated proton-coupled electron transfer in a donor–acceptor supramolecular system12. Issue 5 (29th January 2019) - Ren, Xiaolei; Wang, Xiaohua; Sun, Yuren; Chi, Xiaodong; Mangel, Daniel; Wang, Hongyu; Sessler, Jonathan L.
Abstract : A supramolecular polymer that allows for intrapolymer proton-coupled photoinduced electron transfer was constructed by means of amidinium-carboxylate salt bridges. Abstract : A supramolecular polymer, 3T-DPP, that undergoes photoinduced proton-coupled electron transfer was constructed by means of amidinium-carboxylate salt bridges that serve to link terthiophene electron donors and diketopyrrolopyrrole electron acceptors with a 1 : 1 binding constant of 1.13 × 10 5 M −1 in N -methyl pyrrolidone.